PENGARUH KUALITAS PELAYANAN PAJAK DAN KEPATUHAN MATERIAL WAJIB PAJAK DAN IMPLIKASINYA TERHADAP REALISASI PENERIMAAN PAJAK (SURVEY PADA KPP DI KANWIL DJP JABAR I) - Dwinita, Dian (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2016)
The research was conducted on 7 Tax Offices in West Java Regional Office I. ThePhenomenon is a disappointment related complaints against the service tax, the low ratio of taxcompliance, as well as realization of tax revenues do not reach the target. The purpose of this study is to investigate how the quality of the tax service, influences atasservice quality to compliance materials, influence the quality of the tax service and taxpayercompliance material to the realization of tax revenue in the KPP in West Java Regional Office I. The method used in this research is descriptive and verificative method with quantitativeapproach. The population in this study were 7 KPP in West Java Regional Office I. Respondentsin this study is the Taxpayer at 7 KPP in West Java Regional Office I, a member of the sampleused in this research method is 150 samples. Statistical tests used are Path Analysis, Pearsoncorrelation calculations, the coefficient of determination, test validity, test reliability, and testhypotheses with SPSS 22 for Windows as tool of analysis. The results showed that the variable tax service quality of material tax compliance has a lowrelationship with the direction of a positive relationship. Then the variable of tax service qualityand material tax compliance to realization of tax revenues has a strong relationship with thedirection of a positive relationship.